Q. 35.0( 3 Votes )

Show that y = ae2x + be–x is a solution of the differential equation

Answer :

The differential equation is and the function that is to be proven as solution is

y = ae2x + be–x, now we need to find the value of and .


= 2ae2x – be–x


= 4ae2x + be–x


Putting these values in the equation, we get,


4ae2x + be–x –(2ae2x – be–x) – 2(ae2x + be–x) = 0,


0 = 0


As, L.H.S = R.H.S. the equation is satisfied, so hence this function is the solution of the differential equation.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Interactive Quiz on DIfferential CalculusFREE Class
Functional Equations - JEE with ease48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses